2021
DOI: 10.1177/1759720x21999564
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of Janus kinase inhibitors and biological disease-modifying antirheumatic drugs in rheumatoid arthritis: a systematic review and network meta-analysis

Abstract: Objective: To evaluate the comparative efficacy and safety of Janus kinase (JAK) inhibitors and biological disease-modifying antirheumatic drugs (bDMARDs) in patients with rheumatoid arthritis (RA) and an inadequate response to at least one disease-modifying antirheumatic drug (DMARD). Methods: PubMed, Embase, Cochrane library and ClinicalTrials.gov were searched for relevant randomized controlled trials (RCTs) from inception to April 2020. The active drugs included three JAK inhibitors and eight bDMARDs while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
1
18
0
14
Order By: Relevance
“…Importantly, the proportion of patients reaching remission assessed using the DAS28-CRP was significantly higher in the JAK group than in the case of bDMARDs, which is consistent with the findings of a previous meta-analysis demonstrating the superiority of upadacitinib compared to adalimumab [100]. However, no statistically significant differences were found in remission rates according to the DAS28-ESR, SDAI, and CDAI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, the proportion of patients reaching remission assessed using the DAS28-CRP was significantly higher in the JAK group than in the case of bDMARDs, which is consistent with the findings of a previous meta-analysis demonstrating the superiority of upadacitinib compared to adalimumab [100]. However, no statistically significant differences were found in remission rates according to the DAS28-ESR, SDAI, and CDAI.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, no other meta-analysis examined the effect of JAK inhibitors on PROs, however, some studies included outcomes regarding life quality. One analysis included an improvement in the HAQ-DI and found JAK inhibitors overall as effective as bDMARDs, except for tofacitinib 10 mg showing significant advantage compared to adalimumab and baricitinib 2 mg performing slightly worse than bDMARDs [100]. In our analysis, the different JAK inhibitors were pooled into one group and significant differences between JAK inhibitors versus bDMARDs were not observed either.…”
Section: Discussionmentioning
confidence: 72%
“…In a recent systematic review and network meta-analysis (NMA), comparative efficacy and safety of JAK inhibitors and most of the available bDMARDs were evaluated in RA patients with an inadequate response to at least one DMARD. 27 ACR20, DAS28, and HAQ-DI were used as efficacy outcomes and discontinuations due to AEs for safety. Upadacitinib, tocilizumab, and certolizumab pegol showed relatively good efficacy in these three efficacy outcomes and increasing the doses of JAK inhibitors (baricitinib 4 mg versus 2 mg, tofacitinib 10 mg versus 5 mg, and upadacitinib 30 mg versus 15 mg) did not appear to provide significant additional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The results of in vitro permeation experiments demonstrated that the cumulative permeation and the permeation rates of SIN-MN were 5.31 times and 5.06 times that of sinomenine gel (SIN-G) respectively. Transdermal pharmacokinetic studies in mice showed that the area under the curve (AUC) 0-800 min of the skin and blood of the SIN-MN group were 1.43 times and 1.63 times higher than that of the SIN-G group, indicating that SIN-MN has the ability to enhance the transdermal absorption of the drug (Shu et al., 2020 ).…”
Section: Ra Transdermal Dosage Formmentioning
confidence: 99%